Requirements for nitric oxide production by turbot (Scophthalmus maximus) head kidney macrophages - Tafalla, Carolina; Novoa, Beatriz (Developmental & Comparative Immunology, 2000)
9 páginas, 6 figuras The effect of different cytokines and bacterial lipopolysaccharide (LPS) on turbot (Scophthalmus maximus) macrophage nitric oxide (NO) production has been studied. We have found two different responses concerning NO production in response to LPS. We have studied 43 turbot and only macrophage cultures derived from 30.2% of these turbot were significantly stimulated by LPS. The macrophage populations that did not respond to LPS, showed a constitutive production that was significantly reversed by NO inhibitors like NG-methyl-L-arginine (L-NMMA) and N-ω-nitro-L-arginine (L-NAME), and was dependent on intracellular calcium concentration. We studied the effect of other stimuli combined with LPS on the NO production of these otherwise non-responsive macrophages. LPS combined with turbot macrophage activating factor (MAF) containing supernatants, was capable of significantly stimulating some of these macrophage populations. The same response was observed when LPS was combined with turbot IFN-αβ-like substances. When LPS was combined with human recombinant tumor necrosis factor α (hrTNF-α), the NO production was significantly induced in all macrophage populations studied This research was supported by grant MAR 96-1775 from the Comisión Interministerial de Ciencia y Tecnología (CICYT) (Spain) and also by the British Council (UK) and Ministerio de Educación y Cultura (Spain) through the Coordinated Action HB1998-0175. Peer reviewed